IMPLEMENTASI RESTORATIVE JUSTICE TERHADAP PENYELESAIAN KASUS ANAK BERHADAPAN DENGAN HUKUM DI POLRES MADINA DALAM PERSPEKTIF HUKUM ISLAM - Mhd Dayrobi; Ansari Yamamah; Ramadhan Syahmedi Siregar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research is motivated by the need for a more humanistic approach toward children in conflict with the law compared to the conventional criminal justice system, which tends to be punitive. The main objective of this study is to examine the implementation of restorative justice at the Mandailing Natal Police, identify its supporting and inhibiting factors, and analyze it within the framework of Islamic law. This study employs a qualitative method with a juridical-sociological approach. Data were collected through interviews, observations, and documentation involving law enforcement officers and related parties. The findings reveal that restorative justice has been applied primarily to minor offenses such as theft and minor assault through penal mediation involving the offender, the victim, and their families. Supporting factors include a strong legal foundation and local cultural values that uphold peace and reconciliation, while inhibiting factors consist of limited investigative resources and a lack of public understanding. From the perspective of Islamic law, restorative justice aligns with the principles of islah (reconciliation), afwu (forgiveness), and diyat (compensation), which emphasize the restoration of social relationships and the achievement of communal welfare. Therefore, the implementation of restorative justice at the Mandailing Natal Police reflects a harmony between positive law and the moral values of justice in Islam.